Hunger in the city - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Relationships and solutions in urban poverty, food insecurity and malnutrition.Urban Livelihoods and Food and Nutrition Security in Greater Accra, GhanaD Maxwell, C Levin, M Armar-Klemesu et al., IFPRI. 2000.172 pp.ISBN 0 89629 115 4Free of...